Conceptualizing Interagency Coordination as Metagovernance: Complexity, Dynamism, and Learning in Australian and British Statistical Administration. Issue 6 (11th May 2016) - Howard, Cosmo; Bakvis, Herman
ABSTRACT: Top-down methods of interagency coordination are inadequate in contemporary public administration, where multiple departments and agencies interact across loosely coupled networks to solve complex problems. The concept of metagovernance suggests governments can employ combinations of coordination instruments to steer dispersed actors toward common goals. This article asks how officials in Australian and British statistical administration addressed problems with traditional coordination methods. Interviews with senior official statisticians show a transition from traditional interagency coordination to metagovernance, driven by failures and learning. Metagovernance captures how interagency coordination is increasingly practiced, though existing theories should give more attention to learning and adaptation.